Sustainable transformation of accounting in agriculture - Alrowwad, Anas Mohammad; Alhasanat, Khaled Ahmad; Sokil, Oleh; Halko, Serhii; Kucherkova, Svitlana (Agricultural and resource economics, 2022)
Purpose. The purpose of the article is to model the paradigm of accounting and reporting development in the context of the sustainable agricultural enterprise. Methodology / approach. In the process of working on the article, general scientific methods and methodological techniques were used, in particular, monographic and system analysis (formation of accounting information to take into account sustainable development); methods of comparative analysis (when studying the transition from a traditional accounting system to sustainable accounting); grouping (for grouping accounting types by user groups and information); structural-and-logical compilation (when formulating the conceptual foundations of information to take into account sustainable development); modeling (when building a model of the concept of sustainable accounting and a map of internal and external stakeholders of the enterprise in terms of the level of influence, interest and direction of the formation and use of reporting information); process approach (when developing a paradigm for the development of enterprise reporting in the field of sustainable development); abstract-logical (theoretical generalization and formation of conclusions); graphical method (with a visual display of economic phenomena and processes in time and space); system-functional (to generalize the theoretical and methodological aspects of sustainable development accounting). These methods were the methodological basis of the study. Results. To determine the category of sustainability accounting and the concept of its reporting, the types of entrepreneurial capital were studied, and the characteristics of information that arises as a result of the implementation of economic, social, and environmental activities. In addition, the main users of information, their goals, and their needs were identified. As a result, management and financial accounting for sustainable development were highlighted. The functioning of the institution of sustainable development reporting of agricultural enterprises is based on its "paradigm" as a set of generalized ideas, hypotheses, and methodological approaches shared by the scientific community, acceptable to other institutions, and formalized in the form of scientific theories. In the case when, within the framework of existing theoretical postulates, a scientific institute cannot effectively solve the issues, there is a need to change its paradigm. The proposed paradigm of accounting and reporting will not only orient the development of accounting to the prospects for the transition of mankind to a harmonious economy but also facilitate the acceleration of this transition through the introduction of progressive accounting systems. Originality / scientific novelty. Due to all findings and conducted research in modeling a new system of accounting and reporting for agricultural enterprises we could generate the definition of “sustainability accounting”, which, on the one hand, the segmental, and on the other – the organic component of the enterprise accounting system and the institution of accounting in socio-economic relations, which is organized at the request of the policy of sustainable development, has a corresponding theoretical, methodological and organizational methodological support and is identified in accounting policy, operational, statistical and financial reporting, which provides an organizational and methodological focus on the construction of such accounting by enterprises. Practical value / implications. The main provisions of the article are brought to the level of methodological generalizations and applied tools, the use of which allows adopting a new holistic concept for the formation of accounting and analytical support for the sustainable development of the institutional units of the agrarian sector. The recommendations outlined in the article are fully consistent with modern trends in the development of socio-ecological and economic relations in society, therefore, they can be used in the formation of modern institutional accounting methodology in the context of sustainable development.